Sensitivity to Stimulation, a Component of the Circadian Rhythm in Luminescence in Gonyaulax - Christianson, Roger (1972)
A new method for the stimulation of bioluminescence in the dinoflagellate Gonyaulax polyedra is described. With this technique, in which cells flow through a capillary coil, it is possible to graduate the intensity of the stimulus by varying the flow rate. In continuous darkness, the threshold stimulus for cells in the middle of the day phase is greater than that for cells in the middle of the night phase. Some evidence suggests heterogeneity of sensitivity to stimulation among either cells or individual luminescent sources within a cell. At stimulus intensities much above threshold, the luminescence of both day- and night-phase cells is proportional to the number of cells within the capillary coil. Night-phase cells emit about 14 times as much light as do day-phase cells in continuous darkness. Single bioluminescent flashes from cells were recorded with a high speed camera. No significant difference in flash kinetics was found between cells in the day and the night phase in continuous darkness. Cells in the night phase emit a flash three to five times brighter than that from day-phase cells. About twice as many flashes are recorded in a given time from a population of night-phase cells. The activity of both luciferin and luciferase have been shown to vary rhythmically. The differences in threshold and number of flahses are evidence for a second component of the circadian rhythm in luminescence, a rhythm in sensitivity to stimulation.